Risk factors associated with trastuzumab-induced cardiotoxicity in patients with human epidermal growth factor receptor 2-positive breast cancer - Wesam Abdel-Razaq; Mohammed Alzahrani; Majed Al Yami; Faisal Almugibl; Mohammed Almotham; Razan Alregaibah (Wolters Kluwer Medknow Publications, 2019)
Context: Although trastuzumab is a highly effective and selective targeted therapy for human epidermal growth factor receptor 2 (HER2)-positive breast cancer, the drug-induced cardiotoxicity may confine its usefulness in patients. Aim: To explore risk factors associated with the development of cardiotoxicity in patients with HER2-positive breast cancer. Settings and Design: A retrospective review of medical records and chart review for all patients with breast cancer treated with trastuzumab was conducted at King Abdulaziz Medical City and King Abdullah Specialized Children Hospital in Riyadh, Kingdom of Saudi Arabia, between October 2015 and February 2018. Patients with declined left ventricular ejection fraction, either with or without cardiac symptoms, were recognized as those with cardiotoxicity due to trastuzumab administration. Results: A total of 146 patients were included in the study with an average age of 52.7 (standard deviation = 12.2) years. Thirty-two (21.9%) patients developed cardiotoxicity. However, only 24 (16.4%) were symptomatic with an apparent heart failure but it did not necessitate interruption of trastuzumab therapy. The majority of patients had prior underlying cardiovascular diseases. This study identified unilateral tumor site (62.5%), breast surgery (37.5%), and concomitant taxane chemotherapy (62.5%) as the main risk factors associated with significant increase in cardiotoxicity in patients with breast cancer (with P values of 0.0269, 0.0482, and 0.0225, respectively). Conclusion: The majority of patients (more than 90%) developed cardiotoxicity after completion of chemotherapy. However, recruiting a larger sample size should be warranted to confirm or negate these findings.